Avaliação/Classificação da Disciplina "Seminário": Métodos e Técnicas de Avaliação, estudo realizado no curso de Desporto da Universidade de Trás-os-Montes e Alto Douro - F.J. Gonçalves; A. Aranha (Desafio Singular, 2008)
The central theme of this study is to verify what sort of evaluation the orientactors teachers of the physical education and sport's of monographs of the University of Trás-os-Montes e Alto Douro base their judgement when evaluating (trainee) students of this institution for the subject of seminar. To obtain the information, an anonymous and confidential questionnaire was made for the project. The results were statistically treated by descriptive statistics analyse and content analyse. The obtained results certified that there are orientactors which realise a normative evaluation among the students who have been orientated by them (66,7%), but on the other hand very few orientactors compare the results of their students with the others orientactors students (72,2%). In relation to the criterion of evaluation, all the orientactors (100%) compare the results obtain by their students with criterions established at the beginning of their work. The mystic evaluation (normative and criterion) is realizes by 61,1% of the orientactors. Most of these orientactors (72,2%) realise sumative evaluation, while only 16,7% of the orientactors realise a somative evaluation. Finally 66,7% of the orientactors believe that all the teaching courses should give higher value to the formation in the area of evaluation. Of this percentage, 25% of the orientactors believe that there are no subjects that actually teach how to evaluate.